The Effect of Placing 0.5% Bupivacaine-Soaked Gelfoam in the Gallbladder Bed on Pain after Laparoscopic Cholecystectomy - Saeed, Saeed Dakheel; Al-Dabbagh, Ali A. (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: Patients undergoing laparoscopic cholecystectomy (LC) experiences post operative abdominal pain. This study aimed to determine the character of pain after LC and its relief with 0.5% bupivacaine-soaked gelfoam placed in the gallbladder bed. Methods: A prospective randomized, double blinded placebo-controlled study was conducted on 200 patients with chronic cholecystitis, patients were divided into four groups of 50 patients :group A (2 mg/kg 0.5% bupivacaine-soaked gelfoam kept in gallbladder bed), group B (2 mg/kg 0.5% bupivacaine infiltrated at trocar sites), group C ( 1/2 of the required dose of 2 mg/kg 0.5% bupivacaine infiltrated into the gallbladder bed and at trocar sites, and group D (normal saline in the gallbladder bed and at trocar sites). Postoperatively, the character of pain was noted, and its relief was assessed with verbal rating scale (VRS) scoring. Results: 77.50% of the patients had visceral, 60.50% had parietal, and 23.50% had shoulder pain postoperatively. The visceral pain was significantly less in group A patients than in the control patients (p < 0.01),the mean VRS score at 4, 8, 12 and 24 h in the group A patients also was less than in control group D. Trocar-site infiltration alone was not effective in relieving the parietal pain. Conclusion: Visceral pain is prominent after laparoscopic cholecystectomy and can be effectively controlled by 0.5% bupivacaine-soaked gelfoam in the gallbladder bed alone.